Central Bank Communication and Monetary Policy Effectiveness: Evidence from Nigeria (2013)
The study examines the impact of central bank communication on monetary policy in Nigeria by applying the standard deviation measure of volatility and the vector autoregressive approach. The findings show that inflation and markets volatilities reduced during the period of improved central bank communication. The money market responded positively to central bank communication and reverted faster to equilibrium compared with the stock market which responded negatively and reverted slower to equilibrium. Central bank communication is also able to explain some variation in the money and stock markets. The policy implications of the findings include the need for the Central Bank of Nigeria to continue to improve on its communications strategy as this has helped reduce inflation and markets volatility. In addition, the interest rate channel of the transmission mechanism should be accorder greater priority compared to the asset channel as the money market reverted faster to equilibrium compared to the stock market in the event of a shock.